Narrative Refashioning and Illness: Doctor-Patient Encounters in Siri Hustvedt’s "The Shaking Woman" - Mildorf, Jarmila (Life and Narrative: The Risks and Responsibilities of Storying Experience)

Negotiating Vulnerable Subjects: Margaret Thatcher’s Dementia in Media and Film - Mildorf, Jarmila (Dementia and Subjectivity: Aesthetic, Literary and Philosophical Perspectives)

Dialogic Interactions on Radio: Studs Terkel’s Literary Interviews - Mildorf, Jarmila (Dialogue across Media)

Dialogue across Media: An Introduction - Mildorf, Jarmila; Thomas, Bronwen (Dialogue across Media)

Das Dialoggedicht: Studien zur englischen, deutschen und romanischen Lyrik / Dialogue Poems: Studies in English, German and Romance Language Poetry

Dialogue Across Media

Narrating Selves in Everyday Contexts: Art, the Literary and Life Experience (Style)

Narrating Sounds (Partial Answers)

Hybrid Fictionality and Vicarious Narrative Experience - Hatavara, Mari; Mildorf, Jarmila (Narrative)

The Scott Monument and Scottish Cultural Memory - Ehland, Christoph (Literature and Cultural Memory)

Shoulda, Coulda, Woulda – Non-Canonical Forms on the Move? - Freudinger, Markus (Zeitschrift für Anglistik und Amerikanistik)
Abstract In this paper, the contractions shoulda, coulda, woulda are compared with their respective full forms should have , would have , and could have . Although the full forms are used much more frequently and are, therefore, considered canonical, the non-canonical forms have increased in frequency throughout the better part of the twentieth century. They are predominantly used in American English – in conversation as well as in fictional writing to imitate speech. With respect to their syntactic environment, shoulda, coulda , and woulda behave differently than their full counterparts since they are often used without subjects and without lexical verbs. Some of these uses can be explained by the fact that shoulda, coulda , and woulda are not always used as verbal items but also as nouns, adjectives, and interjections. Due to their overall low frequency and their restriction to a particular register, however, it appears they will keep their non-canonical status for the foreseeable future.
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics

On the Kinda Peripheral Character of Gotta and what we Oughta Do about it - Freudinger, Markus (Exploring the Periphery)

Wie verhalten sich Aktionäre bei Unternehmenszusammenschlüssen? Modellierung sprachlicher Muster zur Analyse treibender Faktoren bei der Berichterstattung - Stotz, Sophia; Geierhos, Michaela (DHd 2016: Modellierung - Vernetzung - Visualisierung. Die Digital Humanities als fächerübergreifendes Forschungsparadigma. Konferenzabstracts, Universität Leipzig, 7. bis 12. März 2016)
Welche Informationen über Unternehmenszusammenschlüsse werden in Zeitungsnachrichten vermittelt, und wie können diese Informationen automatisch extrahiert werden? Dies soll am Beispiel des Verhaltens von Aktionären während eines Zusammenschlusses ermittelt werden. Dazu werden die wichtigsten Aussagen über das Votum der Aktionäre im Hinblick auf eine automatische Erkennung sprachlich analysiert. Im Fokus stehen dabei die Berichte über Aktionärsabstimmungen hinsichtlich der Annahme bzw. Ablehnung eines Übernahmeangebots.

Webmonitoring - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Webmonitoring

Sentimentanalyse - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Sentimentanalyse

Text Mining - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Text Mining

Crawler (fokussiert / nicht fokussiert) - Geierhos, Michaela (Enzyklopädie der Wirtschaftsinformatik)
Keywords: Crawler

On- and Off-Topic Classification and Semantic Annotation of User-Generated Software Requirements - Dollmann, Markus; Geierhos, Michaela (Proceedings of the 2016 Conference on Empirical Methods in Natural Language Processing (EMNLP))
Users prefer natural language software requirements because of their usability and accessibility. When they describe their wishes for software development, they often provide off-topic information. We therefore present an automated approach for identifying and semantically annotating the on-topic parts of the given descriptions. It is designed to support requirement engineers in the requirement elicitation process on detecting and analyzing requirements in user-generated content. Since no lexical resources with domain-specific information about requirements are available, we created a corpus of requirements written in controlled language by instructed users and uncontrolled language by uninstructed users. We annotated these requirements regarding predicate-argument structures, conditions, priorities, motivations and semantic roles and used this information to train classifiers for information extraction purposes. The approach achieves an accuracy of 92% for the on- and off-topic classification task and an F1-measure of 72% for the semantic annotation.

40 issues of ICAME News/ICAME Journal - Mindt, Ilka (ICAME Journal 40)

An interview with Joybrato Mukherjee, the Chair oft he ICAME Board - Kytö, Merja; Stenström, Anna-Brita; Mindt, Ilka (ICAME Journal 40)